Morphological evolution of the vertebrate forebrain: From mechanical to cellular processes. Issue 6 (23rd August 2019) - Aboitiz, Francisco; Montiel, Juan F.
Abstract: Although the cerebral hemispheres are among the defining characters of vertebrates, each vertebrate class is characterized by a different anatomical organization of this structure, which has become highly problematic for comparative neurobiology. In this article, we discuss some mechanisms involved in the generation of this morphological divergence, based on simple spatial constraints for neurogenesis and mechanical forces generated by increasing neuronal numbers during development, and the different cellular strategies used by each group to overcome these limitations. We expect this view to contribute to unify the diverging vertebrate brain morphologies into general, simple mechanisms that help to establish homologies across groups. Abstract : Developmental topography of major pallial regions in different vertebrates, indicating the arrangement of radial glia and pathways of radial cell migration from the ventricular zone. RESEARCH HIGHLIGHTS: Mechanical forces constrain brain morphogenesis Cellular mechanisms evolve to minimize these constraints This produces morphological divergence across vertebrates, challenging homology